IUI: review and systematic assessment of the evidence that supports global recommendations. (14th February 2018) - Cohlen, Ben; Bijkerk, Aartjan; Van der Poel, Sheryl; Ombelet, Willem
Abstract: BACKGROUND: IUI with or without ovarian stimulation (OS) has become a first-line treatment option for many infertile couples, worldwide. The appropriate treatment modality for couples and their clinical management through IUI or IUI/OS cycles must consider maternal and perinatal outcomes, most notably the clinical complication of higher-order multiple pregnancies associated with IUI–OS. With a current global emphasis to continue to decrease maternal and perinatal mortality and morbidity, the World Health Organization (WHO) had established a multi-year project to review the evidence for the establishment of normative guidance for the implementation of IUI as a treatment to address fertility problems, and to consider its cost-effectiveness for lower resource settings. OBJECTIVE AND RATIONALE: The objective of this review is to provide a review of the evidence of 13 prioritized questions that cover IUI with and without OS. We provide summary recommendations for the development of global, evidence-based guidelines based upon methodology established by the WHO. SEARCH METHODS: We performed a comprehensive search using question-specific relevant search terms in May 2015. For each PICO (Population, Intervention, Comparison and Outcomes) drafted by WHO, specific search terms were used to find the available evidence in MEDLINE (1950 to May 2015) and The Cochrane Library (until May 2015). After presentation to an expert panel, a further hand search of references in relevant reviews was performed up to January 2017. Articles that were found to be relevant were read and analysed by two investigators and critically appraised using the Cochrane Collaboration's tool for assessing risk of bias, and AMSTAR in case of systematic reviews. The quality of the evidence was assessed using the GRADE system. An independent expert review process of our analysis was conducted in November 2016. OUTCOMES: This review provides an assessment and synthesis of the evidence that covers 13 clinical questions including the indications for the use of IUI versus expectant management, the sperm parameters required, the best and optimal method of timing and number of inseminations per cycle, prevention strategies to decrease multiple gestational pregnancies, and the cost-effectiveness of IUI versus IVF. We provide an evidence-based formulation of 20 recommendations, as well as two best practice points that address the integration of methods for the prevention of infection in the IUI laboratory. The quality of the evidence ranges from very low to high, with evidence that may be decades old but of high quality, however, we further discuss where critical research gaps in the evidence remain. WIDER IMPLICATIONS: This review presents an evidence synthesis assessment and includes recommendations that will assist health care providers worldwide with their decision-making when considering IUI treatments, with or without OS, for their patients presenting with fertility problems.